الإلتزامات المترتبة على عقد الإعلان الإلكتروني - الساعدي, جليل حسن; محمد, فاطمة نجم (Journal of Legal Sciences, 2019)
The continuous development in the field of information and communication systems led to the emergence of many new contracts for the processing of Internet services and how to use them, Which is the online advertising contract some kind of them. Nowadays, the internet is considered one of the most important media advertising for products and services comparing to what traditional advertising services present, a lot of advertisers are resorting to publish their ads electronically , Their means of doing so is to contract with an online publisher or an e-advertising agency that in turn contracts the publisher for the same purpose , The electronic advertising contract entails a set of obligations on both the publisher and the online advertiser , One of the most prominent obligations of an online publisher is the commitment to electronic media before contracting , And commitment to provide electronic advertising service and commitment to provide confidentiality of the profession , The obligation of the online advertiser is to be obliged to pay cash , The obligation to provide the electronic publisher with information necessary for the performance of the advertising work and the obligation to review and accept the electronic advertisement .